Reaktywacje dystopii w najnowszej literaturze popularnej. Na marginesie lektury powieści Margaret Atwood i Ignacego Karpowicza = Reactivation of dystopia in the latest popular literature. On the sidelines of reading the novels by Margaret Atwood and Ignacy Karpowicz - Piechota, Dariusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Dystopia seems to be one of the most popular motifs in the latest pop culture. One of the reasons for it is that political, economic, and social transformations have happened in many countries.
Keywords: dystopia; powieść; politycy; dyskryminacja; novel; violence; politicians; discrimination